The Practice Path of Building the Modern Civilization of the Chinese Nation in the New Era and New Journey - Liu, Xiaoyuan (International Journal of Social Sciences and Public Administration, 2024)
The modern civilization of the Chinese nation is a new form of human civilization created by the Communist Party of China (CPC) in the historical process of advancing Chinese-style modernization, which has united and led the Chinese people. It embodies the distinctive spiritual symbol of the Chinese nation and embodies the spiritual strength of the Chinese people to be confident and self-reliant. From the theoretical foundation, cultural foundation and youth strength of the construction of the modern civilization of the Chinese nation, this paper explores the practical path of realizing the goal of cultural power in the new era and new journey, in order to provide reference and reference for the construction of the modern civilization of the Chinese nation.